Land use change and environmental-economic impacts of toll road development and urbanization: a scopus-based systematic review - Antomi, Yudi; Angraina, Dila; Arif, Dian Adhetya (Indonesian Indovisi Institute, 2025)
Toll road development is a major driver of land use transformation, especially in rapidly urbanizing regions such as Southeast Asia, China, and Sub-Saharan Africa. However, evidence linking toll roads to land conversion, environmental degradation, and economic change remains fragmented and is largely based on observational and cross-sectional studies, limiting causal interpretation. This systematic review synthesizes empirical findings on land use change, environmental and economic impacts, and implications for sustainable corridor planning. Following PRISMA 2020, a Scopus search (2017–2026) identified 1,086 records, with 50 studies included after screening. Results show that toll roads accelerate the conversion of agricultural land into urban and industrial uses, with conversion rates reaching 47.8% in Indonesia. Ecosystem service values decline by 8–23% within 5 km of new expressways. Economic impacts vary, with Chinese studies showing improved land-use efficiency, while African and Southeast Asian contexts reveal increased spatial inequality. A major finding of this review is that the current evidence base remains insufficient to establish strong causal relationships between toll road development and observed environmental-economic outcomes due to the dominance of cross-sectional and non-experimental study designs. This review proposes the Corridor-Mediated Land Transformation (CMLT) framework and recommends stricter land regulation within 5 km of toll interchanges. Future research should apply longitudinal quasi-experimental designs to clarify causal relationships and strengthen policy relevance.